Kajian Status Gizi, Imunisasi Bacillus calmette guerin (BCG), dan Kondisi Lingkungan Rumah dengan Kejadian Tuberkolosis pada Bakita di Kecamatan Mlati Sleman - Noviana Setyaningsih; Idi Setiyobroto; Supartuti Supartuti (Poltekkes Kemenkes Yogyakarta, 2016)
Background :Indonesia is number fourth highest Tuberculosis burden country after China, India and South Africa. Now a days, tuberculosis in children is growing rapidly. At least 500,000 children in the world suffer from TB every year. TB is an infectious disease caused by Mycobacterium tubercolosis. Generally, TB attacks lungs, but can spread to other organs in the body. Many factors that can influence TB disease are nutritional status, vaccination and environmental housing condition. Objective : This research aims to examine the relationship between nutritional status, Bacillus Calmette-Guerin (BCG) vaccination and environmental housing condition with TB in toddlers in Mlati Sleman. Methods :The type of this study was observational research with case control study match by sex and age design. It was done in June 2015 and located in Mlati. The subjects of research were 18 toddlers with TB in Mlati I and II clinics. The control sample was collected using purposive random sampling with ratio 1:1 for toddlers who did not suffer from TB. The independent variables were BCG vaccination, nutritional status and environmental housing condition and the dependent variable was TB in toddlers. Data were collected by interviews, measurement and observation of the environmental housing condition of the respondents. The data were analyzed using univariate and bivariat statistical tests (Chi-Square test and OR). Result : immunization coverage BCG reaches 100%. Conclusion :There is a relationship of the incidence of TB with the nutritional status of toddlers in Mlati (p < 0.05). The Condition of the home environment include flooring, lighting, windows, toilets, garbage and water are not related to the incidence of TB in Mlati (p > 0.05). Keyword: TB in toddlers, nutritional status, BCG vaccination, environment housing condition